Proposta para aproveitamento das águas de drenagem de subsolo: o rebaixamento do lençol freático no bairro de Moema - Ferreira, Wagner Buck (2011)
In urban areas, where there are more than 80% of the population, the problem of water supply is critical. Unplanned urbanization, illegal occupations, the bad social conditions, poor water use or difficult access to public services and infrastructure, are responsible for the growing compromising of the springs, and no less serious health problems. An important source of supply is groundwater, which is currently being used inappropriately by their use or by its inconsistent exploitation, coupled with the fact severe sources of contamination threat this important feature. In Sao Paulo, where many buildings are located in flat areas, and topographically low, corresponding to the floodplains of streams, it is often necessary to lower the water table for the construction of basements below it and subsequent maintenance of operating conditions of these basements. These downgrades cause impacts on groundwater abstraction (wells) and settlements in the soil around it, besides releasing large amounts of water into public storm drainage system. The aim here is to show the importance of water, the waste and neglection practiced with the groundwater drawdown in groundwater in buildings in Moema in Sao Paulo